The Effectiveness of Reality Group Counseling to Improve Self-Control - Tangkua, Dessy Margathyfera; Eddy Wibowo, Mungin; Purwanto, Edy (Universitas Negeri Semarang, 2022)
Self-control is important for students due to its impact on the learning process, self-control, and academic goals pursuit. This study aimed to determine the self-control level of SMA Teuku Umar students in Semarang. It used an experimental method with the design of randomized pretest-posttest control group and involved 14 students with low self-control level. Based on the results of Wilcoxon Signed Rank and Mann-Whitney tests, the intervention of reality group counselling has been effective to improve students’ self-control. Further implications and limitations are discussed in the discussion section.